Rodeo ranch : a Western duo - Brand, Max, 1892-1944 (Five Star, a part of Gale, Cengage Learning, 2015)
"Doc Willis, despite the nickname, is just an unemployed cowboy in The Valley of Jewels. Daggett Valley holds many secrets from the past, including a now deserted mining camp. It is there that Buck Logan lures Willis with the promise of great riches to be gained. What Doc doesn't even suspect is that he is to play a part in a most subtle feat of deception in which an old man, William Daggett, will be conned into believing that he is reliving his past. Rodeo Ranch is so called because of the rodeos sponsored by Ramon Alvarez. When an attempt is made on Alvarez's life, a rodeo is held, but the only event that interests him is the shooting competition. The event is won by Duds Kobbe, who is hired to be Alvarez's body guard. What Kobbe doesn't realize is that he will be just as much a target as Alvarez. "--